Ebola preparedness in the Western Pacific Region, 2014 - Xu Zhen; Boris I Pavlin; Raynal C Squires; Thilaka Chinnayah; Frank Konings; Chin-Kei Lee; Li Ailan (World Health Organization Regional Office for the Western Pacific, 2015)
West Africa is currently experiencing the largest outbreak of Ebola virus disease (EVD) in history with intense transmission in several affected countries. For non-affected countries, the best protective measures are adequate levels of preparedness including vigilant surveillance to detect cases early and well-prepared health systems to ensure rapid containment of the virus and to avoid further spread. The World Health Organization Regional Office for the Western Pacific recently conducted two activities: a web-based EVD preparedness survey and an EVD simulation exercise to determine the overall level of EVD preparedness in the Region. The survey and exercise together demonstrate there is a good overall level of preparedness for a potential imported case of EVD in the Western Pacific Region. However, a number of areas still require further strengthening before the Region can efficiently and effectively respond to potential EVD events, including laboratory testing arrangements; clinical management and infection prevention and control; and public health intervention measures, particularly at points of entry. Importantly, the survey and exercise also highlight the unique situation in Pacific island countries and emphasize that special considerations are needed to better support these countries in EVD preparedness.